2016
DOI: 10.1161/jaha.115.003076
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Heart Disease With and Without Cyanotic Potential and the Long‐term Risk of Diabetes Mellitus: A Population‐Based Follow‐up Study

Abstract: BackgroundLong‐term survival for persons born with congenital heart disease (CHD) is improved, but limited knowledge exists of this growing population's acquired cardiovascular risk profile. This study's purpose was to assess CHD survivors’ risk for type 2 diabetes mellitus (T2DM) with attention to the impact of cyanotic CHD.Methods and ResultsThis population‐based cohort study included Danish subjects with CHD who were born between 1963 and 1980 and were alive at age 30 years. For each CHD case, we identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…289 A population-based study from Denmark showed new onset of DM in 4% between 30 and 45 years of age with a hazard ratio of 1.35 of new DM in adults with CHD compared with the general population. 303 This study noted that this risk was concentrated in individuals with repaired cyanotic CHD (hazard ratio, 2.85), although the reasons remain unclear. Impaired glucose tolerance and prediabetes have been demonstrated in almost 40% of adults with CHD.…”
Section: Diabetes Mellitusmentioning
confidence: 93%
“…289 A population-based study from Denmark showed new onset of DM in 4% between 30 and 45 years of age with a hazard ratio of 1.35 of new DM in adults with CHD compared with the general population. 303 This study noted that this risk was concentrated in individuals with repaired cyanotic CHD (hazard ratio, 2.85), although the reasons remain unclear. Impaired glucose tolerance and prediabetes have been demonstrated in almost 40% of adults with CHD.…”
Section: Diabetes Mellitusmentioning
confidence: 93%
“…Decreased glucose tolerance on oral glucose tolerance test (OGTT) is more common in patients with complex ACHD compared with healthy controls . Furthermore, register studies have reported a higher prevalence of diabetes mellitus in patients with ACHD compared with controls . Patients with ACHD have an increased risk of metabolic syndrome compared with controls and obesity is as common in patients with ACHD as in the general population .…”
Section: Introductionmentioning
confidence: 99%
“…Though, it is well known that patients with CCHD are limited in their physical activity due to their chronic hypoxia. A recent published study showed that patients with CCHD have an increased risk of developing type 2 diabetes mellitus 34. Among the four studies on CCHD and atherosclerosis (figure 1), Ciftel et al and Duffel et al reported no difference in body mass index 6 7.…”
Section: Possible Antiatherosclerotic Factors In Cchdmentioning
confidence: 98%